Epidemiologia genômica de Campylobacter jejuni e Campylobacter coli no Brasil: Avaliação em um contexto Sul-Americano - Buiatte, Ana Beatriz Garcez (2024)
Campylobacter jejuni and Campylobacter coli are frequently associated with human gastroenteritis worldwide, being transmitted through the consumption of contaminated water or animal-derived food, particularly chicken meat. C. jejuni is more prevalent and virulent, while C. coli harbors more antibiotic resistance genes. Brazil is among the largest producers of chicken meat globally, but few genomic studies have been conducted on these pathogens in the country, and little is known about the genetic relationship of Campylobacter spp. isolated in Brazil with isolates from South America. This thesis is divided into three chapters, with the first chapter providing general considerations to contextualize the reader regarding the topic addressed in the subsequent chapters. The second chapter presents an epidemiological and evolutionary analysis of 221 C. jejuni genomes isolated in Brazil between 1996 and 2018. Resistance and virulence genes were investigated, and MLST profiles were determined. A phylogenetic tree was also constructed using the maximum likelihood method. C. jejuni isolates from chickens presented more resistance genes than those from humans and monkeys. Virulence genes associated with Guillain-Barré Syndrome were identified in genomes from chickens, humans, and monkeys, with the highest prevalence in ST353. Multi-drug resistance determinants, including quinolones, beta-lactams, tetracyclines, macrolides, aminoglycosides, streptothricin, and arsenic resistance were identified. ST353 was the most prevalent lineage throughout the study period, found in both chickens and humans, and was subjected to a time-calibrated phylogenetic analysis. The most recent common ancestor of ST353 was estimated to have emerged in 1592, coinciding with the post-discovery period of Brazil, when Portuguese settlers introduced chickens to the country. At least two transmission events from chickens to humans were identified, indicating that socioeconomic changes in poultry farming contributed to the expansion of the C. jejuni clonal population in Brazil. The Brazilian genomes were compared with 374 C. jejuni genomes from South America, revealing a diverse population, with CC353 being the most prevalent. The third chapter focuses on the population analysis and spread of resistance determinants in 190 C. coli genomes which were isolated in South America between 1995 and 2022. MLST profiles, resistance genes, and the presence of mobile genetic elements (MGEs) were determined. A phylogenetic tree was constructed using the maximum likelihood method. C. coli of CC828 was the most prevalent in South America. Resistance determinants related to aminoglycosides, tetracyclines, lincosamides, and multi-drug resistance were identified associated with MGEs. While plasmids were important MGEs in Brazil and Ecuador, in Peru, transposable elements were more frequently associated with antimicrobial resistance determinants. Points of mutation were associated with resistance to macrolides and quinolones, while genes related to efflux pumps and beta-lactams were identified only on the chromosome. Collectively, these findings demonstrate the relationship between C. jejuni and C. coli with the poultry production chain, and the potential risk of antimicrobial resistance dissemination. Campylobacter spp. populations are widely spread throughout South America and can exchange genetic material through various mechanisms. Given the public health risks, efforts should be made to enhance surveillance and monitoring of these pathogens in Brazil and Latin America.